PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Empiris pada Perwakilan BKKBN Provinsi Jawa Tengah) - Elmi Rosita Darmawati, 16.05.62.0005; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
This research entitled “Application of Performance-Based Budgeting affect to Performance Accountability Government Institution (Empirical Study on Representative Office of BKKBN Central Java Province)”, purposed to analyze the influence of budget planning, budget implementation, budget reporting, and performance evaluation to performance accountability on Representative Office of BKKBN Central Java Province. The population of this study were 157persons. Sampling was conducted using a purposive sampling method and number of samples were 47 respondents. Primary data collection method used in this study, and analyzed by multiple regression model.The result showed that budget planning, budget implementation, and performance evaluation have a positive and significant influence to performance accountability. Meanwhile budget reporting has a negative and significant influence to performance accountability.Keywords: performance-based budgeting; budget planning; budget implementation; budget reporting; performance evaluation; performance accountability.